Analysis of Engineering Student Retention Based on Math Placement and Performance - Serkan Varol; Zachary Ridder (Journal of College Orientation, Transition, and Retention)
Colleges face a demographic downturn in the total number of students incoming students, and within engineering programs, retention is particularly challenging due to the rigor of the curriculum. Mathematical proficiency has repeatedly been cited as a common indicator of engineering student success and retention within the major. This research aims to explore if math placement, and performance in mathematics courses, is a significant predictor of their fall-to-fall retention at the University of Tennessee at Chattanooga. Using a logistic regression model, and including math placement test scores, math course grades, and other independent variables associated with student retention, the results of this study showed that only in the first year of attendance was math placement a significant predictor of engineering retention.